Hubungan Kemampuan Adaptasi Kerja dengan Penerapan Kesehatan dan Keselamatan Kerja Perawat - Astawa, I Made Adi; Wati, Ni Made Nopita; Wati, Ketut Lisna (Holistic Nursing and Health Science, 2023)
The Hospital occupational health and safety programs’ objectives to guarantee and protecting the nurses’ health and safety. However, nurses need to adapt regarding the working conditions to implement the nursing service optimally.   This study aims to identify the relationship between the nurses' working adaptability and the implementation of occupational health and safety among associate nurses.  This study was a quantitative study employed a cross-sectional design. The sampling technique employed in this study was purposive sampling with a sample size of 103  associate nurses choosen by using inclusion and exclusion criteria. The instruments employed to measure adaptability and application of occupational health and safety was questionnaires that has been tested for validity and reliability. This study has been ethically approved through ethical clearance number 070/5630/RSUDW.  The data analyzed employed in this study was Rank Spearman Correlation test. The study results found that the majority of nurses showed have a good working adaptability (86 peoples;83,5%), the occupational health and safety implementation (88 peoples, 85,4%) by p-value = 0.000; r = 0.780 which means there is a significant relationship between the nurses' working adaptability and the implementation of occupational health and safety with a strong positive relationship. Nurses are expected to implement occupational health and safety optimally in order to improve the quality of nursing care services delivered to patients.